Dry Port Location Factor Determination using Delphi in Peninsular Region - G Mohan, Vidya; Nasser, MA (Transactions on Maritime Science, 2022)
Locating a dry port depends on various criteria such as distance, modes of transport, cost associated, environmental, geographical, and social concerns. The paper's primary purpose is to identify the location-specific attributes impacting dry port locations, particularly in peninsular India, where seaports are very close to each other. The paper's objective has been achieved through a four-cycle Delphi survey and criticality through linear ranking and consistency through Kendall’s ‘W’. Initially, the criteria are identified through a systematic literature survey. They are then sieved within a focus group consisting of five experts with experience of more than twenty years in port operations. Final vetting of the criterion is done through a Delphi survey; the experts with a mutual interest in the subject but from different backgrounds are included. The final vetted list is determined. In the last two rounds of the survey, the rankings were determined, a consensus was reached, and the final rank was obtained. The results indicate that proximity and economic criteria are the most crucial in the chosen geography, which contradicts the developed regions, where the environmental criterion dominates. However, the environmental criteria have been ranked third. Even though the Delphi method is an age-old method used in many literatures in different contexts, it is not used in a dry port problem in the peninsular region. Consensus building is significant in strategic decisions, like dry port location selection. Since this study involves multiple stakeholders from diverse backgrounds and a subjective opinion was required, the Delphi method and linear ranking have been adopted.